PSYCHOLOGICAL ANALYSIS OF THE REFLECTIVE DEVELOPMENT PROCESS OF STUDENTS IN MILITARY ACADEMIC LYCEUMS - Ergashev Doniyor (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This article analyzes the process of reflective development among students of military academic lyceums (“Temurbeklar Maktabi”), its psychological characteristics, and main components. The study employed theoretical analysis, psychological diagnostic methods, and systematic review of developmental psychology sources. The findings revealed that reflective development manifests through intellectual, emotional, and personal reflection. The Luscher test, logical problem-solving tasks, and social portrait analysis are effective tools for identifying students’ emotional states, thinking processes, and the influence of the social environment. The development of reflective processes contributes to students’ responsibility, self-awareness, and professional formation as military personnel.